Nucleophosmin and p14ARF mediated regulation of p53 - Abraham, A (2015)
Tumour initiation and progression occur due to oncogenic mutations that also contribute to therapeutic resistance in many human tumours. Mutations activating the "PI3K/AKT" signalling pathway and inactivating the "TP53" tumour suppressor gene are common mechanisms that cancer cells require to proliferate and escape pre-programmed cell death. p53 mutant (p53mut) tumours not only fail to respond to DNA damaging therapy, but are also described to promote therapeutic resistance by dominant negative suppression of p53 dependent promoter activity. Our work identifies the crucial interaction between the PI3K/AKT pathway and p53 mutations that regulate treatment sensitivity in tumours. Using a combination of in vitro and in vivo techniques we demonstrate that AKT inhibition promotes reduced cellular levels of p53mut via a novel Nucleophosmin 1 (NPM) mediated regulation of the tumour suppressor p14ARF and promotes re-engagement of cell cycle arrest, senescence and increased sensitivity to ionising radiation in both in vivo and in vitro systems. We show that the PI3K/AKT pathway plays an important role in the regulation of p53mut and inhibitors of this pathway can re-sensitise treatment resistant tumours. This has helped us to simultaneously highlight the cohort of patients where the greatest efficacy may be achieved in clinical practise. We further show that the AKT mediated regulation of NPM that we describe in solid tumours is relevant in Acute Myeloid Leukaemia (AML) with mutated NPM, albeit showing physiologically different effects. This further highlights the necessity for rational treatment planning with the newer targeted agents that inhibit specific signalling pathways in AML patients.